The Effect of Nano-Zinc Oxide and Nano-Titanium Dioxide on Inhabitation of Ochratoxin A - Al-Saji, Layla R.; Al-Nazzal, Ahmed I. (Iraqi Journal of Science, 2021)
The experiment was conducted at the Agricultural Research Office in Baghdad during July 2020 to test the ability of nanomaterials (ZnO and TiO2) to inhibit ochratoxin A, which is produced by a number of microbiology (fungi) including: Aspergillus ochraceus, A. niger, ,A. steynii, A. carbonarius, Pencillume verrucosum and P. nordicum. The standard ochratoxin A, with known concentration, was treated with different concentrations of nanomaterials (20, 40, 60, and 80 ppm) and two different particle sizes of nanoparticles approximately (15 nm) and (70 nm) for each (ZnO) and TiO2; with 16 transactions. Through an examination of the HPLC, the results showed that all transactions led to a noticeable inhibition in the concentration of ochratoxin A, and the highest inhibition rate was for ZnO nanoparticles with particle-size (70 nm) and 80 ppm concentration, where the inhibition rate was 99%. In other hand, the TiO2 nanoparticles with particle-sized (70 nm) and the concentration (80 ppm) were followed by 95%.